Analisis Efektivitas dan Faktor-Faktor yang Mempengaruhi Penerimaan Pajak Hotel di Kabupaten Nabire Papua - Tunjanan, Letarius (JURNAL ADMINISTRASI BISNIS (JAB), 2020)
This study aims to analyze the factors that influence hotel tax revenues in the Nabire Regency of Papua. The results of the study showed that the hotel tax contribution in 2014 and 2018 was not as expected by the government, especially Nabire Regency. So that autonomy ordinance in the province of Papua can be optimal and successful, a fair planning and use of tax process is needed as from the legal authority and responsible and implemented in accordance with the mechanism of tax use.